The analysis of barriers to bim implementation for industrialized building construction: a China study - Wu, Ping; Jin, Ruoyu; Xu, Yidong; Lin, Feng; Dong, Yiting; Pan, Zhihong (Journal of Civil Engineering and Management, 2021)
The emerging Building Information Modeling (BIM) can better promote the development of building industrialization, with data integration between information-rich building models and business processes. However, the practical implementation of BIM still faces barriers. Existing studies have discussed these barriers extensively, but the research on the barriers to the implementation of BIM amid building industrialization in China is inadequate. In this study, 23 barriers were identified through literature review. A questionnaire survey approach was used to collect data from various parties. Factor analysis methods were used to process and rank barrier factors for BIM applications in the context of industrialized building. Based on the analysis of each factor, analytic hierarchy process was adopted to identify the key barriers to the implementation of BIM for industrialized building construction. The study concluded that the main barriers for BIM implementation for industrialized building were capital-related factors and the lack of support from owners. This study proposes that in addition to governmental policy support for BIM and multi-stakeholder engagement, companies should also organize experts to effectively evaluate the risks of applying BIM. Overall, this study provides suggestions on construction organizational transformations in the roadmap of moving towards digital-driven building industrialization.